AIGC-Empowered Teaching Reform and Practice in Cultural Creative Product Design - Tan , Jiawei; Wang, Xiaoxia (Journal of Educational Theory and Practice, 2026)
Against the backdrop of rapid AIGC (AI-Generated Content) technological development and the intelligent transformation of higher education, design education is undergoing profound structural changes. Traditional courses like Ethnic Cultural Creative Design have long been constrained by dilemmas such as "superficial cultural understanding," "inefficient creative generation," "lagging technology application," and "simplified evaluation systems," making it difficult to meet the cultural and creative industry’s demand for interdisciplinary talent. Based on the latest research in educational technology, higher education pedagogy, and theories of educational change, this paper constructs a three-dimensional "culture-technology-design" integrated curriculum reform framework. It proposes a human-AI collaborative teaching model with AIGC at its core and develops an actionable practical teaching path within real classroom settings. The research indicates that AIGC, serving as a "creative partner," can significantly enhance students’ depth of cultural decoding, efficiency of idea generation, and quality of technology application. The "dual-mentor guidance + AI collaboration" model facilitates learners’ identity shift from "technology users" to "human-AI co-creative designers." The construction of a multi-dimensional evaluation system enables systematic assessment of the learning process, cultural value, and degree of technological integration. This reform practice holds significant implications for the paradigm shift in higher education design programs, the sustainable development of culture, and the construction of smart education.